1997
DOI: 10.1002/(sici)1096-9861(19970224)378:4<522::aid-cne7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of nitric oxide synthase in the cerebral ventricular system, subfornical organ, area postrema, and blood vessels of the rat brain

Abstract: The distribution of neuronal nitric oxide synthase (nNOS) has been studied in the more rostral portion of the lateral ventricle, subfornical organ, area postrema and blood vessels of the rat central nervous system. nNOS was located by means of a specific polyclonal antibody, by using light and electron microscopy. Light microscopy showed immunoreactive varicose nerve fibers and terminal boutons-like structures in the lateral ventricle, positioned in supra- and subependimal areas. The spatial relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 66 publications
2
15
0
1
Order By: Relevance
“…On the other hand, due to the intensive DAB reaction distributed in the entire axoplasm, the association of NOS to vesicle membranes in presynaptic profiles was not excluded either by the authors describing the cytoplasmic location of NOS (Aoki et al, 1993;Atkinson et al, 2003). Others have emphasized that in preparations of high quality the cytoplasmic NOS-IR material was clearly located around synaptic vesicles (Rodrigo et al, 1997;Sancesario et al, 2000). In accordance with the aforementioned literature data our findings with those from the literature would suggest the association of NOS with the vesicle membranes,.In addition, according to their location and the ultrastructural appearance of the labeled vesicles, the NADPH-d reactive and NOS-IR vesicles seem to represent identical types.…”
Section: Specificity and Identity Of The Demonstration Of Nadph-d Andsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, due to the intensive DAB reaction distributed in the entire axoplasm, the association of NOS to vesicle membranes in presynaptic profiles was not excluded either by the authors describing the cytoplasmic location of NOS (Aoki et al, 1993;Atkinson et al, 2003). Others have emphasized that in preparations of high quality the cytoplasmic NOS-IR material was clearly located around synaptic vesicles (Rodrigo et al, 1997;Sancesario et al, 2000). In accordance with the aforementioned literature data our findings with those from the literature would suggest the association of NOS with the vesicle membranes,.In addition, according to their location and the ultrastructural appearance of the labeled vesicles, the NADPH-d reactive and NOS-IR vesicles seem to represent identical types.…”
Section: Specificity and Identity Of The Demonstration Of Nadph-d Andsupporting
confidence: 87%
“…From this point of view it is rather strange why only a single study has dealt until now with fine details of the localization of NOS (Johansson et al, 1996), in contrast to vertebrates (Rodrigo et al, 1997;Aoki et al, 1998;Rothe et al, 1998;Sancesario et al, 2000;Seress et al, 2005). At light microscopic level NOS was found mainly in sensory-and interneurons, and less in motor neurons of invertebrates, and it seemed that NO mainly acts in an anterograde way (Park et al, 1998;Wildemann and Bicker, 1999;Serfőző et al, 2008).…”
Section: In Invertebratesmentioning
confidence: 99%
“…Using immunohistochemical methods to detect the localization of nitric oxide, however, Rodrigo et al [48] demonstrated the presence of positively stained cell bodies and fibers in several areas in the rat brain; i.e. the globus pallidus, the red nucleus, the principal sensory trigeminal nucleus and the locus coeruleus.…”
Section: Distribution Of Nadph-d-positive Neuronsmentioning
confidence: 99%
“…Although a great deal of attention has been paid to the distribution of the 5-HT neurons in the circumventricular organs [58], and recently also to that of NOS [48], there have been few studies concerning the relationship between NOS and 5-HT neurons in the circumventricular organs. The possibility that the nitergic fibers regulate metabolic function in the wall of the ventricular system, and that 5-HT-positive fibers do the same in the subfornical organ, has been discussed [48]. The functions of the circumventricular organs have not yet been elucidated.…”
Section: Considerable Relationship Between Nadph-d-positive Neurons Amentioning
confidence: 99%
See 1 more Smart Citation